Bahasa Inggris - Setyawan, Adi; Laksana, Rio Dhani; Pujiwati, Ami (Jurnal Akuntansi, Manajemen dan Ekonomi, 2024)
Changes in the global economy require every organization to increase effectiveness in carrying out its activities. Likewise, organized universities have three important components in facing global change, namely organizational commitment, organizational culture, and strategic management. An organization in carrying out its activities cannot be separated from its employees. An employee's performance can be influenced by various factors such as the work environment, infrastructure, production, health, level of work safety, and mutual understanding which will lead them in one direction so that they have a maximum level of performance to achieve organizational goals. . The theory used in this research is goal setting theory. This type of research is quantitative research which will also be explained through descriptive statistical analysis. The population and sample of this research are Open University employees who have minimal education and are located in Central Java - Yogyakarta. This research instrument uses a questionnaire which is calculated using a Likert scale, then the data will be processed using an application called SmartPLS. The results of this research state that overall the strategic performance measurement system variables, organizational commitment, and organizational culture have a significant effect on role stressors. Furthermore, it is hoped that the results of this research can become a reference for organizations to continue to improve their managerial performance while still paying attention to the variables that can influence it